Hydrologic and hydraulic response to wildfires in the upper Cache la Poudre watershed using a SWAT and HEC-RAS model cascade - Havel, Aaron, author; Arabi, Mazdak, advisor; Baker, Daniel, committee member; Wohl, Ellen, committee member (Colorado State University. Libraries, 2015)
The enhanced possibility of catastrophic wildfires in the western USA and other regions around the world has increased the need to evaluate the effects of wildfire on the hydrology of watersheds and the hydraulic behavior of rivers. Understanding the effects of wildfires is vital in water-resources management and for public safety especially in regions where communities depend on surface water supply. Similarly, areas adjacent to river systems may be at risk of increased flooding due to wildfires in their upstream watersheds. Effects of wildfires on hydrologic fluxes in watersheds and rivers have been extensively studied; but, characterization of responses to wildfires is difficult due to the spatial variability of post-wildfire conditions. At the watershed scale, hydrologic responses comprise a network of complex nonlinear interactions. Hence, comprehensive watershed models serve as a useful tool to understand these relationships. Watershed models commonly lack the ability to represent channel geometry and channel process with sufficient spatial frequency. Thus, a hydrologic and hydraulic model cascade provides a bridge between the nonlinear interactions of the uplands and the river responses at the channel scale. The overall goal of this study is to examine the spatial variability of the effects of the 2012 High Park and Hewlett wildfires that occurred within the headwaters of the Cache la Poudre River located in northern Colorado, USA. Two commonly used models were calibrated and used in combination. First, the Soil and Water Assessment Tool (SWAT) was used to evaluate the hydrologic responses of the upper Cache la Poudre watershed to the wildfire events. Subsequently, the results from the SWAT model were used as inputs for the hydraulic model Hydrologic Engineering Center River Analysis System (HEC-RAS) to simulate channel hydraulics along 42.5 km of the upper Cache la Poudre River. The baseline SWAT model was established to simulate the hydrology of the study area between the years 2000 and 2014. This model accounts for wildfires by modifying land use/land cover inputs and corresponding parameters during simulations. Daily streamflow data were used for model calibration and testing. Using the calibrated baseline model, no-wildfire and wildfire scenarios were created. The two scenarios were then compared for changes in average annual total runoff volume, water budgets, and full streamflow statistics at the watershed and sub-basin scales. Then a HEC-RAS model was developed to simulate the hydraulic responses of the stream network using streamflows for various floods extracted from the two SWAT scenarios. High resolution DEM data and surveyed water surface elevations are used for model calibration and testing, respectively. Channel hydraulic behavior including flood inundation area, streamflow velocities, and channel shear stress were compared for the two scenarios at the channel scale. At the watershed scale, wildfire conditions have little effect on the hydrologic responses, but at the sub-basin scale a total runoff increase up to 75 percent between scenarios was found. Generally, wildfire affected water budgets showed more surface runoff versus subsurface runoff, suggesting a decrease in infiltration rates under post-wildfire conditions. Flow-duration curves developed using full streamflow statistics for burned sub-basins show that less frequent streamflows become greater in magnitude leading to ecosurplus values up to 0.279. Also, simulations revealed that there is a strong and significant (R2 > 0.8 and p < 0.001) positive correlation between runoff increase and percentage of burned area upstream. Streamflow increases were between 2 and 14 percent depending on the reach’s proximity to the wildfire and the flood. Lastly, along the main stem only slight increases in flood area, average cross section velocity, and shear stress as a result of wildfire were observed in the simulations. The results have important implications on improving post-wildfire water resources management.
Keywords: burn severity; hydraulic modeling; hydrologic modeling; wildfires